Modelling of home appliances using fuzzy controller in achieving energy consumption and cost reduction - Parvin K.; Al-Shetwi A.Q.; Hannan M.A.; Jern K.P. (Kauno Technologijos Universitetas, 2023)
While home energy prices keep rising, homeowners nowadays are searching for the right options to reduce their electricity bills. Besides, the increase in power consumption can contribute to environmental pollution. Therefore, the proper management of energy in the domestic sector is a vital element for creating a sustainable environment and cost reduction. In this study, the most domestic household appliances consumption of energy are modelled and analysed using the fuzzy logic controller (FLC) in order to permit the home energy management system (HEMS) to perform energy utilization estimation and cost analysis. These appliances are the heating ventilation and air conditioning (HVAC), electric water heater (EWH), and lighting, respectively. The developed system can help to analyse the appliances' energy consumption and cost sceneries during peak and off-peak hours. The modelling of a fuzzy-based domestic appliances controller for HEMS takes the peak and non-peak tariff of Malaysian grid into consideration. The simulation results demonstrate that the developed models are able to manage energy consumption and cost reduction efficiently. By using the proposed FLC, the cost of energy is reduced by 21.75 %, 30.77 %, and 41.96 % for the HVAC, EWH, and dimmable lamps, respectively. In sum, the FLC shows good performance to reduce the cost and power consumption toward efficient HEMS. 2021 Kauno Technologijos Universitetas. All rights reserved.